2003
DOI: 10.1046/j.0266-4909.2003.00030.x
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual tools for planning for the wireless classroom

Abstract: Wireless and mobile devices are beginning to offer stunning new technical capabilities for collaborative learning. Yet, researchers in this field must recognise the importance of complementing these technical advances with improved understanding of the patterns of classroom activity that most need support. The approach taken in the work reported in this paper has been to create conceptual tools that help thinking and talking about technology‐supported collaborative learning. A particularly powerful tool is Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 2 publications
0
14
0
5
Order By: Relevance
“…Early investigations of interactive handheld use outlined a number of promising designs for classroom collaboration (i.e., DiGiano, Yarnall, Patton, Roschelle, Tatar, & Manley, 2003, Pinkwart, Hoppe, Milrad, & Perez, 2003. Kaput (2000) notes that such instructional designs for networked devices inherit long pedagogical traditions of classroom activity, organized at one of three levels-the whole (teacher-led) class, small groups, or individual students.…”
Section: Supporting Collaboration Through Classroom Networkmentioning
confidence: 99%
“…Early investigations of interactive handheld use outlined a number of promising designs for classroom collaboration (i.e., DiGiano, Yarnall, Patton, Roschelle, Tatar, & Manley, 2003, Pinkwart, Hoppe, Milrad, & Perez, 2003. Kaput (2000) notes that such instructional designs for networked devices inherit long pedagogical traditions of classroom activity, organized at one of three levels-the whole (teacher-led) class, small groups, or individual students.…”
Section: Supporting Collaboration Through Classroom Networkmentioning
confidence: 99%
“…The recent advances in mobile technology have paved the way for mobile learning, hereafter m-learning (DiGiano, et al, 2003). The literature review for this chapter found no consensus about the current state of m-learning.…”
Section: Mobile Learningmentioning
confidence: 88%
“…Following this first step, each group has to take into account the global discussion and adapt each solution in order to make it coherent with it. DiGiano, Yarnall, Roschelle, Tatar and Manley define eight Collaboration Design Patterns for classroom activities in a wireless classroom [9,10]. Each pattern describes a collaborative pedagogical scenario.…”
Section: Contributions Of New Technologies To Pedagogical Activities mentioning
confidence: 99%
“…Today, mobile and wireless devices are extensively included in new pedagogical organizations [9,10]. The frontiers of the classroom are not clearly defined [4,6,11].…”
Section: Introductionmentioning
confidence: 99%